استخدام Tell Me More لترقية مهارة الاستماع - Jannah, Ida Mifatkhul; Nu’man, Muhammad; Mansur, Muhammad; Islam, Mohammed; Faiza, Nais Musyafaul (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2022)
Based on the results, learning listening skills carried out by teachers using the sam’iyah syafahiyah method and using cassette media. However, many students do not understand the material being taught because the teacher is less attractive in presenting listening skills material. Therefore, the researchers tried to use the media in the form of Tell Me More Arabic software to improve students’ listening skills. Tell me More Arabic is an interactive and well-designed Arabic learning software. This software can help learning Arabic language skills including listening, speaking, reading and writing skills.